Pedagogy strategy to foster creativity and innovation in the product design process/ Shaira Ismail ... [et al.] - Ismail, Shaira; Abd Rahman, Nurul Hayani; Shafie, Nani Ilyana; Md Yusoff, Mohd Sukor (2023)
This study concentrated on the pedagogical strategy to foster creativity and innovation among the science and technology students at the UiTM Pulau Pinang Branch. 46 degree-seeking students from the Faculty of Mechanical Engineering made up the sample for this study. They are required to invent technology-based products or services as part of the ENT600 entrepreneurship course. The case study collected data during the product design process. The method used to generate ideas was based on the product design process. Students learn about entrepreneurship and develop their entrepreneurial abilities through creating technology-based products and services. This promotes an understanding of technology-based entrepreneurship that blends theoretical and real-world perspectives. For the course, students are required to complete practical project-based assignments that involve developing cutting-edge technology products and services. Presentations, group projects, case studies, and lectures are some of the teaching methods used. The product design process improves students' ability to think critically and values the impact on their comprehension of how to address problems by designing for problem-solving, improving, altering, and changing through questioning to design solutions.